Utilization of existing genetic variability - Smithson, James Brady (Southern Africa Development Coordination Conference (SADCC), 1989)
The diversity of bean producing areas in Africa in terms of environments and cropping systems and the nature of existing cultivars are briefly described. The lengths of growing seasons and rainfall, temperature and photoperiod during the growing seasons of bean producing areas are being characterized. These have been combined into an index to map the distributions of areas of similar growing conditions in Latin America and Africa. Research stations may be classified in a similar manner. Such classifications require refining but are important in directing flows of germplasm and breeding materials between Latin America and Africa and within African national programmes. Knowledge of genotypic responses to environments is necessary to support such classifications. Evaluation of common sets of genotypes across locations and seasons, for example the African Bean Yield Adaptation Nursery (AFBYAN), is one means of obtaining such knowledge. Recent introductions have exhibited dramatic improvements in performance over existing cultivars. Possible strategies for the evaluation of local and introduced germplasm and breeding materials are discussed. (AS)